Registro de un coyote (canis latrans) blanco en el desierto chihuahuense de Durango, México - López González, Carlos A. (Instituto de Ecología, A.C., 2011)
The presence and geographic location of a white-colored coyote in the Chihuahuan Desert of Durango, Mexico is recorded.